(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Incorporating guava leaf powder into chocolate is a creative way to boost its nutritional profile and potentially add a unique flavour. Guava leaf powder, being rich in soluble dietary fibre and vitamin C, can indeed enhance the health benefits of chocolate. Soluble dietary fibre can aid in digestion and promote gut health. Thus, the present study was to achieve an innovative formulation, i.e., guava leaf chocolates containing guava leaf extract and effective ingredients, which could be a way to entrap all the benefits of the guava leaf into an easy-to-consume formulation by increasing patient compliance and therapeutic outcomes. Response Surface Methodology (RSM) has been used here to optimise the formulation. RSM allows us to systematically vary the levels of these ingredients and analyse their impact on sensory attributes such as taste, texture, aroma, hardness, and overall acceptability. The use of various batches (F1 to F15) suggested a systematic approach to formulation adjustment, likely involving tweaking ingredient proportions and processing parameters to achieve the desired sensory attributes. The inclusion of physico-chemical analysis confirmed the stability of the formulation, ensuring product quality and consistency. And the results were felt within satisfactory a range, which indicates that the formulation was stable and suitable for its intended purpose, potentially for therapeutic applications. Furthermore, highlighting the eco-friendliness, ease of handling, and positive sensory attributes such as sweetness and flavour can contribute to the overall appeal of the product. By meeting these criteria, the formulation not only meets functional requirements but also aligns with consumer preferences and environmental considerations.